Beyond Immunity: Underappreciated Functions of Intestinal Macrophages - Chiaranunt, Pailin; Tai, Siu Ling; Ngai, Louis; Mortha, Arthur (Frontiers in Immunology, 2021)
The gastrointestinal tract hosts the largest compartment of macrophages in the body, where they serve as mediators of host defense and immunity. Seeded in the complex tissue-environment of the gut, an array of both hematopoietic and non-hematopoietic cells forms their immediate neighborhood. Emerging data demonstrate that the functional diversity of intestinal macrophages reaches beyond classical immunity and includes underappreciated “non-immune” functions. In this review, we discuss recent advances in research on intestinal macrophage heterogeneity, with a particular focus on how “non-immune” functions of macrophages impact tissue homeostasis and function. We delve into the strategic localization of distinct gut macrophage populations, describe the potential factors that regulate their identity and functional heterogeneity within these locations, and provide open questions that we hope will inspire research dedicated to elucidating a holistic view on macrophage-tissue cell interactions in the body’s largest mucosal organ.